2003
DOI: 10.1016/s0098-1354(03)00067-x
|View full text |Cite
|
Sign up to set email alerts
|

Combining prior knowledge with data driven modeling of a batch distillation column including start-up

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…neural networks. The biggest advantage of Fuzzy models, when compared to more data-driven techniques, is that they are interpretable, wherefore they can offer transparency in situations where physical models are difficult to derive (van Lith et al, 2002(van Lith et al, , 2003. However, for their derivation considerable more knowledge is required than for other data-driven models.…”
Section: Operational Knowledge -Rule Based Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…neural networks. The biggest advantage of Fuzzy models, when compared to more data-driven techniques, is that they are interpretable, wherefore they can offer transparency in situations where physical models are difficult to derive (van Lith et al, 2002(van Lith et al, , 2003. However, for their derivation considerable more knowledge is required than for other data-driven models.…”
Section: Operational Knowledge -Rule Based Informationmentioning
confidence: 99%
“…The integration of Fuzzy models along with first-principles knowledge can, as before, be accomplished in parallel (Abonyi et al, 1999;Fu & Barford, 1995b) or in series (van Lith et al, 2002(van Lith et al, , 2003Vieira, Dias, & Mota, 2005). Moreover they can be complementarily combined into an existing hybrid approach, e.g.…”
Section: Operational Knowledge -Rule Based Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have reported the potential and benefits derived from the use of hybrid systems for fault detection and diagnosis, combining fundamental process knowledge with data-base models (Van Lith et al, 2003;Venkatasubramanian et al, 2003c;Nandi et al, 2004;Van Sprang et al, 2005;Thornhill and Horch, 2007;Yang and Xiao, 2012), especially when considering large-scale industrial situations. From a model-based perspective, it has been shown that the use of hierarchical system decomposition, as a qualitative model-based reasoning tool, can provide effective modularity for structuring large-scale diagnostic knowledge bases (Prasad et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Examples are found in the literature that span from the simple cases of partially linear models [7] and semi-physical modeling [10], in which physical insights are used to design suitable nonlinear transformations of part of the inputs, to more problem-specific cases in which prior knowledge about the physics of the process under observation is embedded in the model [5,17].…”
mentioning
confidence: 99%